X+(x-4)+4(x-4)=52

Simple and best practice solution for X+(x-4)+4(x-4)=52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+(x-4)+4(x-4)=52 equation:


Simplifying
X + (x + -4) + 4(x + -4) = 52

Reorder the terms:
X + (-4 + x) + 4(x + -4) = 52

Remove parenthesis around (-4 + x)
X + -4 + x + 4(x + -4) = 52

Reorder the terms:
X + -4 + x + 4(-4 + x) = 52
X + -4 + x + (-4 * 4 + x * 4) = 52
X + -4 + x + (-16 + 4x) = 52

Reorder the terms:
-4 + -16 + X + x + 4x = 52

Combine like terms: -4 + -16 = -20
-20 + X + x + 4x = 52

Combine like terms: x + 4x = 5x
-20 + X + 5x = 52

Solving
-20 + X + 5x = 52

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + X + 20 + 5x = 52 + 20

Reorder the terms:
-20 + 20 + X + 5x = 52 + 20

Combine like terms: -20 + 20 = 0
0 + X + 5x = 52 + 20
X + 5x = 52 + 20

Combine like terms: 52 + 20 = 72
X + 5x = 72

Add '-5x' to each side of the equation.
X + 5x + -5x = 72 + -5x

Combine like terms: 5x + -5x = 0
X + 0 = 72 + -5x
X = 72 + -5x

Simplifying
X = 72 + -5x

See similar equations:

| 7t=xfort | | 2(y+2)=6y | | f(x)=-4x^2+6x+9 | | x-4+x=90 | | 8.5*2+7.5*2=c*2 | | 0.2(7+2t)=t+1.4 | | -5x^4*-2x^4= | | 6x^2-22x+20=0 | | -3x+7x=5(x+3)-(x+15) | | 9(8c-9)=-81+72c | | -34+z=-59 | | Z+8=9 | | -(-6y-4z-2)= | | x^2-0.6x+0.09= | | 3x=6x-4 | | 10sec^2x-10=7tanx+2 | | 2n/11=-23 | | 14+2/3e=8 | | Z-2=3 | | x+2x+15= | | 5+4e=37 | | 18s^3=50s^3 | | -x+9=24 | | 175000+550T=220650 | | x-40+x=90 | | 5/8=2x+1/8 | | 4k-11=8k+29 | | 35000+1680T=300440 | | 14+w=98 | | 8x^2+36x-13=0 | | y=0.15x^3-5x^2+7 | | 35000+1680T=300400 |

Equations solver categories